Unveiling phytochemical diversity and safety profile of hot water extract from Tetrapleura tetraptera fruit - Chukwuma Raphael Ekeanyanwu; Chinelo Chinenye Nkwocha; Chidinma Lynda Ekeanyanwu (BMC Complementary Medicine and Therapies)
Abstract Background Tetrapleura tetraptera, a widely used medicinal plant in West Africa, has been traditionally employed for various ailments. Despite its folkloric significance, scientific validation of its safety and potential neuroactive properties remains limited. Objectives This study aimed to investigate the acute and subchronic toxicity of Tetrapleura tetraptera hot water extract (HWETTF) in rats and to elucidate its phytochemical composition. Methods Acute oral toxicity was assessed in mice using the OECD guideline 423, while a 14-day repeat-dose toxicity study was conducted in rats. The phytochemical analysis included HPLC, FT-IR, and GC–MS. Results HWETTF exhibited no significant toxicity in acute or subchronic studies, even at high doses. Phytochemical analysis revealed a diverse array of compounds, including those with potential GABAergic and CNS depressant activities. Conclusion Tetrapleura tetraptera demonstrated a favourable safety profile in rodents and possesses a rich phytochemical composition. Further research is warranted to explore its potential neuroactive properties and develop therapeutic applications.